Towards the development of cost-effective point-of-care diagnostic tools for poverty-related infectious diseases in sub-Saharan Africa - Ofori, Benedict; Twum, Seth; Nkansah Yeboah, Silas; Ansah, Felix; Amofa Nketia Sarpong, Kwabena (PeerJ, 2024)
In this review, we examine the current landscape of point-of-care testing (POCT) diagnostic tools designed for poverty-related infectious diseases (PRIDs) in sub-Saharan Africa (sSA) while delineating key avenues for future advancements. Our analysis encompasses both established and emerging diagnostic methods for PRIDs, addressing the persistent challenges in POCT tool development and deployment, such as cost, accessibility, and reliability. We emphasize recent advancements in POCT diagnostic tools as well as platforms poised to enhance diagnostic testing in sSA. Recognizing the urgency for affordable and widely accessible POCT diagnostic tools to detect PRIDs in sSA, we advocate for a multidisciplinary approach. This approach integrates current and emerging diagnostic methods, explicitly addressing challenges hindering point-of-care (POC) tool development. Furthermore, it recognizes the profound impact of misdiagnosis on public and global health, emphasizing the need for effective tools. To facilitate the successful development and implementation of POCT diagnostic tools in sSA, we propose strategies including the creation of multi-analyte detection POCT tools, the implementation of education and training programs, community engagement initiatives, fostering public-private collaborations, and the establishment of reliable supply chains. Through these concerted efforts, we aim to accelerate the development of POCT in the sSA region, ensuring its effectiveness and accessibility in addressing the diagnostic challenges associated with PRIDs.
Keywords: Resource-limited settings; Diagnostic tools; Point-of-care testing (POCT); Diagnosis; Sub-Saharan Africa (sSA); Poverty-related infectious diseases (PRIDs)